2023
DOI: 10.1080/22423982.2023.2175763
|View full text |Cite
|
Sign up to set email alerts
|

Traditional crafting as a catalyst for Indigenous women’s intergenerational cohesion and wellness: a Canadian perspective

Abstract: Indigenous crafting practices are increasingly being recognised for their benefit to community connectedness, health, cultural identity, and individual wellbeing. This article explores published literature to determine the role of Indigenous crafting in transferring traditional and cultural teachings from female relatives and Elders to girls and younger women. We examine the effect of crafting on intergenerational cohesion and social connectedness within the Indigenous community. Does crafting serve as an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The review was undertaken with recognition that cultures around the world, particularly indigenous knowledge systems, have long understood and operationalized understanding of how art participation contributes to social cohesion and well-being in communities (56, 57). This indigenous understanding is articulated in a recent study in Canada, which reported that 53.7% of Indigenous residents surveyed reported that the arts are very important to social connection compared with 23.8% of non-Indigenous respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The review was undertaken with recognition that cultures around the world, particularly indigenous knowledge systems, have long understood and operationalized understanding of how art participation contributes to social cohesion and well-being in communities (56, 57). This indigenous understanding is articulated in a recent study in Canada, which reported that 53.7% of Indigenous residents surveyed reported that the arts are very important to social connection compared with 23.8% of non-Indigenous respondents.…”
Section: Discussionmentioning
confidence: 99%